Pengembangan Model Penilaian Autentik Kompetensi Berbicara - Rahmawati, Laili Etika; Fatimah, Nuraini (Universitas Muhammadiyah Surakarta, 2014)
The first year research has aim to: (1) describe the learning assessment process of the speaking theory subject and (2) design the theorethic model of authentic assessment in speaking competence. The method used in the research is Research and Development method, i.e. the research method is used to produce certain product, and to test the effectiveness of the product. The results of the research are: (1) the assessment activity of the studentsâ speaking competence who takes the speaking theory subject have the characteristics of authentic assessment. It is based on the result of the curriculum review which has impact to the syllabus adjustment in directing to the teachersâ need at school. Therefore, the speaking competence assessment which focuses on the speaking ability, nowadays its academic competence focus is broading. In addition, the audiencesâ affective respon is used as the assessment consideration; (2) the theoretic model of speaking competence assessment can be described that the speaking competence assessment is divided as two step categories, they are the process and the result assessment. The portofolio assessment is the most theorithic assessment tecnique which considered as it appropriate to gain the studentsâ speaking competence development. The result of the assessment is divided into two tests, i.e the middle semester test and the final semester test. The middle semester test is used to know the studentâs competence which has closed relation to the speaking theories because the students have to mastery the speaking competence in order to practice the speaking competence, the studentsâ must also have to teach it. The final semester test is conducted to know the studentsâ competence in the speaking practice which can be conducted by the three techniques, they are group, peer, and individual technique. The tehcniques can be applied based on the needs and the characteristic of the tested competence.